Effectiveness of Using CT Scan in EarlyDetection of Brain Tumor - M. Arif Budiman; Yayat Suharyat; Sisi Yulianti; Abdul rahman (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The aim of this research is to determine the effectiveness of using CT Scans in Early Detection of Brain Tumors. The type of research is meta-analysis research. The data sources in this research come from 11 national and international journals published in 2021-2024. Inclusion criteria in the meta-analysis are research from indexed journals SINTA, EBSCO, Copernicus International and Scopus, research obtained from the Google Scholar, Pubmed, Researchgate, Mendeley and ScienceDirect databases, research related to the effectiveness of using CT scans in early detection of brain tumors, research must be an experimental method or experimental method, and research that has complete data in effect size analysis. Data analysis is calculating the effect size value with the help of Revman 5.1. The research results concluded that the average effect size value was 1.17 with a high effect size category. These findings explain that the use of CT Scans has a positive impact in early detection of brain tumors in humans.